Heralds of Doom - Burtch, Andrew (Material Culture Review, 2012)
Abstract From the early Cold War until the mid-1960s, government and military agencies moved to purchase and install air raid sirens across the country, as part of a program to prepare Canada for nuclear war. The sirens transformed everyday public sites into often unwelcome reminders of the ever-present threat of nuclear war. The siren network was dismantled at the end of the Cold War, yet, in the past five years, “rediscovery” of sirens has generated debate over whether to restore and repurpose the alarms for commemorative display or to discard them as a legacy of the absurdity of nuclear survival plans. This study, using recently released archival sources, presents the material history and cultural impact of the Canadian air raid siren.